Evaluation of New Fungicides for the Management of Mango Anthracnose Disease Caused by Colletotrichum Gloeosporioides - H Rahman; A Akter; M M Rahman; M M Islam; R Momotaz; T H Tabassum; M Nazneen; Salma Sarker (International Journal of Trends in Horticulture, 2026)
A field experiment was conducted at the field of Plant Pathology Division, Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Jamalpur-2000, Bangladesh during February to July 2024 to assessment the efficacy/effectiveness of thirty-five (35) new fungicides received from Pesticide Technical Advisory Committee (PTAC), Bangladesh with control treatment against anthracnose disease of mango. Most of the fungicides under inspection were able to control the disease successfully. This study suggests that fungicidal spray significantly affected the development of anthracnose in mangoes. Most of the fungicides used in this study were successful in preventing anthracnose, but they all decreased the disease's incidence and severity to varying degrees when compared to the control. Efficacy of different new fungicides ranged from 68.65 to 99.17%. Thirty-five (35) fungicides inhibited the disease by over 90%. However, only five (5) fungicides were able to inhibit the disease by less than 80%. Regarding the effectiveness of several new fungicides, the following efficient fungicidal treatments are recommended in order of higher to lower efficacy: Azoxystrobin 20% + Difenoconazole 12.5% SC > Carbendazim 50% WDG > Trifloxystrobin 25% + Tebuconazole 50% WDG > Tricyclazole 75% WP > Mancozeb 50% + Carbendazim 25% 75 WP. Most of the fungicides that were being studied were successful in controlling the disease. According to the study, fungicides that managed the disease increased fruit yields and, as a result, yielded the highest profits. Azoxystrobin 20% + Difenoconazole 12.5% SC was the most effective spray over control, followed by Carbendazim 50% WDG and Trifloxystrobin 25% + Tebuconazole 50% WDG. The findings demonstrated the benefits of controlling mango anthracnose with fungicides. The best methods to prevent mango anthracnose and guarantee effective mango cultivation, according to the mango producers, are to spray Azoxystrobin 20% + Difenoconazole 12.5% SC, Carbendazim 50% WDG, and Trifloxystrobin 25% + Tebuconazole 50% WDG.
Keywords: Anthracnose disease; colletotrichum gloeosporioides; correlation study; disease incidence; disease severity; efficacy of different new fungicides; mango; yield (kg/plant)